Cleaning House? Assessing the Impact of Maine’s Clean Elections Act on Electoral Competitiveness - Powell, Richard (Maine Policy Review, 2010)
Does full public financing of legislative elections make races more competitive? Richard Powell analyzes the impact of the Maine Clean Elections Act (MCEA) on Maine House and Senate elections since its passage in 2000. Using statistical analysis, he concludes the MCEA has not significantly increased competitiveness, even though candidates have been able to rely substantially less on private contributions and the financial disparity between candidates has decreased significantly. Powell suggests that analysis of the Maine case will be useful as the nation and other states consider public-financing laws comparable to the MCEA.
Keywords: Maine Clean Elections Act; public funding of elections